Simultaneous Measurement and Compositional Analysis of Atmospheric Microplastics in Taiwan Utilizing Optical and Chemical Methods - Yen Shun Hsu; Wei Hsu Kao; Yu Cheng Chen; Zhen Shu Liu; Yuan Cheng Hsu; Po Jen Wu; Ying Hui Wang; Kai Hsien Chi (Aerosol and Air Quality Research)
Abstract Microplastics (MPs) have emerged as a critical global environmental concern. This study investigated atmospheric MPs in Taiwan from April to December 2021 across three sites—Rural, Municipal Waste Incinerator (MWI), and Traffic—using a 25 μm size threshold. MPs were identified using μ-FTIR and Py-GC–MS. Concentrations were highest at the Traffic site (0.26 #/m3), followed by MWI (0.15 #/m3) and Rural (0.13 #/m3), with no detection at the background site (Mt. Lulin). Dry and wet deposition fluxes ranged from 4.29 to 11.8 #/m2/day. Polyethylene (PE), Polypropylene (PP), and Polyamide (PA) were the most common polymers, with site-specific variations suggesting sources such as traffic, incineration, and industrial activities. Py-GC–MS detected PE, PTFE, PEI, and various additives. Estimated human exposure via inhalation ranged from 0.031–0.131 #/kg-bw/day, and ingestion from 0.010–0.335 #/kg-bw/day. These findings highlight the presence of airborne MPs in both urban and rural environments, underlining the need for regulatory action and further research on health impacts. Graphical Abstract